Next-Gen Authentication Public Transport System Using Smart QR Codes - Dnyaneshvar Suryavanshi; Pratik Shipalkar; Arkas Shivam; Prof. Vyavahare V. A.; Dr Divekar S. N. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
With the rapid evolution of urban mobility, traditional authentication methods for public transport are becoming inefficient and vulnerable to security risks. This paper proposes a Next-Generation Authentication System utilizing Smart QR Codes to enhance security, efficiency, and user convenience in public transportation networks. The system leverages dynamic QR codes, which change periodically to prevent fraudulent duplication, ensuring secure access for passengers. By integrating cryptographic encryption, cloud-based validation, and real-time monitoring, the proposed system enhances passenger authentication while reducing operational bottlenecks. Additionally, machine learning techniques can be incorporated for anomaly detection, identifying unauthorized access attempts and improving fraud prevention mechanisms. The smart QR-based system is cost-effective, easy to deploy, and provides seamless integration with existing transport infrastructure, making it a scalable solution for modern smart cities.
Keywords: Smart QR Codes; Next-Generation Authentication; Public Transport System; Dynamic QR Code; Secure Ticketing; Fraud Prevention; Cryptographic Encryption; Real-Time Monitoring; Machine Learning for Authentication; Urban Mobility Solutions; Passenger Flow Management; Smart Cities; IoT in Transportation